Ambivalently post-lesbian: LBQ friendships in the rural Midwest. Issue 1 (2nd January 2018) - Forstie, Clare
ABSTRACT: Using data from friendship interviews with lesbian, bisexual, and queer women in a small Midwestern city, I argue that non-urban communities might be characterized as ambivalently post-lesbian, as participants explain that shared identities "don't matter" in their friendships, while continuing to insist on the relevance of lesbian identity in their community. This research highlights three sets of concerns about lesbian communities, identities, and friendships. First, given the theoretical purchase of the concept of "post-gay" communities, there is a parallel need to develop the concept of "post-lesbian" as uniquely ambivalent and distinct from post-gay discourses, as the case of LBQ friendship demonstrates. Second, the appearance of post-lesbian narratives beyond major cities suggests a need to reassess the presumably progressive post-gay narrative that gay identities are becoming less central to gay lives. Finally, a focus on close lesbian friendships highlights the central role such relationships continue to play in constituting, and perhaps dismantling, lesbian identities and communities.